Civil defendant representation in criminal proceedings - M. М. Kolomoitsev (Bulletin of Kharkiv National University of Internal Affairs)
The article determines that a representative of a civil defendant may be involved in criminal proceedings after a civil claim is filed, and if it is established that the defendant is proper, it becomes possible to exercise the right of a civil defendant to representation.